(3eSCdI aj ehVY Gdabjg Hjf jOi GdeOQSs - (3CHj HcQ Hf hdj GdOjf Hf bGVj YLdhf GdTGaYj, Jbj GdOjf,J (B928 (3g` s
(3ChdgG (B:s
(3GdMeO ddg heG Jhajbi EdG HGddg s
(3BNQgG (B:s
(3fYhP HGddg ef TQhQ CfaSfG hSjFGJ CYeGdfG hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfi YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs